Kemampuan Menulis Lanjutan (Kelas Tinggi) dalam Perspektif Pendidikan Inklusi - Nurfadhillah, Septy; Khanifah, Nurul; Enjelina, Sindi (Lembaga Yasin AlSys, 2026)
This study aimed to provide an in-depth description of the extended writing skills of fourth-grade students at SDN Pondok Bahar 3 within an inclusive education context. A qualitative approach was employed using observation, interviews, and documentation with three students—AJ, PB, and BA—who exhibited different characteristics and learning abilities. The analyzed aspects included the ability to express ideas, coherence between sentences, paragraph organization, vocabulary selection, and the use of spelling and punctuation. The findings show that AJ demonstrated extended writing skills in the fairly good category, with a relatively coherent structure of writing, although technical linguistic errors were still identified; PB was categorized as fair, characterized by the ability to construct simple sentences but not yet able to develop ideas optimally; whereas BA fell into the category requiring intensive support due to difficulties in expressing ideas and forming complete sentences. These findings underscore that extended writing abilities among students in inclusive classrooms are highly diverse, thereby necessitating the implementation of differentiated instruction and adaptive assessment to more optimally support the development of all students’ writing skills.